Complete mitogenome of the biocontroller fungus Purpureocillium sp. (Ascomycota, Ophiocordycipitaceae, Hypocreales) (2018)
The strain Purpureocillium sp. UdeA0106 is an antagonist of nematodes, fungi, and garden symphylans from crops with high economic importance in Colombia (Salazar 2013; Salazar et al. 2014; Cardona et al. 2014; Gallego et al. 2014) and is being studied to be proposed as new species. It was included on the 1000 fungal genomes project to elucidate its phylogenetic relationships with other fungi. Purpureocillium’s mitogenome has 23,495 bp of circular size. It contains 15 protein-coding genes without duplications (PCGs), corresponding to the 60% of its total length, 23 transfer genes (7.6% tRNA), two of them duplicated (trnR and trnM), and two ribosomal genes (17.6% rRNA) and a GC content of 28.44%. A phylogenetic tree was proposed using their 14 PCGs mitochondrial genes and was compared with other fungi of the Subphylum Pezizomycotina. Phylogenetics relationships showed UdeA0106 to be close to P. chlamydosporia and M. anisopliae forming a cluster with other fungal biocontrol agents and separated the strain of plant pathogenic fungi. © 2018, © 2018 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.